STRENGTHENING SELF-EXPRESSION OF PERSONS WITH DISABILITIES THROUGH FILM SCRIPTWRITING TRAINING AT RUMAH VOKASI HANENDA - Sri Wastiwi Setiawati; Cito Yasuki Rahmad; Ahmad Fajar Ariyanto; Rizqullah Ramadhan Panggabean (Yayasan Education and Social Center, 2026)
The short film scriptwriting training for persons with disabilities, organized by Rumah Vokasi Hanenda in collaboration with the Indonesian Institute of the Arts (ISI) Surakarta, aims to enhance narrative literacy, creativity, and inclusive participation of people with disabilities within the filmmaking ecosystem. The program was implemented through a community-based empowerment approach that positioned participants as active subjects using methods such as discussion, hands-on practice, and production. The activity involved 11 participants from 10 special-needs schools (SLB) in Yogyakarta, supported by 12 accompanying teachers who served as adaptive facilitators. The training materials covered ideation, premise development, character building, and the writing of simple scripts, all adjusted to the needs of deaf, blind, and intellectually disabled participants. The outcomes demonstrate improvements in the participants’ scriptwriting skills, self-confidence, and creative expression. The four scripts produced reflect human values, inclusion, and the participants’ lived experiences. This program not only strengthens individual capacities but also fosters a collaborative space that promotes authentic representation of disability in film. The initiative serves as an inclusive learning model that can be replicated to empower people with disabilities in the arts and cultural sector.